Gestational Age, Socioeconomic Context and Infection-Related Hospital Admissions of Infants Born With Gestational Age Less Than 33 Weeks. Issue 12 (2nd September 2022) - Berland, M; Boucekine, M; Fayol, L; Tardieu, S; Nauleau, S; Garcia, P; Boubred, F
Abstract: Using data from a regional medical follow-up network database of preterm infants born with gestational age (GA) <33 weeks, we found that low GA and deprived socioeconomic neighborhoods increased incidence of infection-related hospitalization during the first year of life. Respiratory tract infections rates were higher in extremely preterm infants.